Sociopsychological diagnostics of personality and group through the example of the business game «Boat» - A. Avdeeva; Y. Safonova (Вестник университета)
The article presents the experience of developing the discussion business game "Boat". The goals of the game are directed on the development of social competence of hearing impaired students in an inclusive environment and are realized through а complex psychodiagnostics, didactically and educational tasks. The projective content of the game scenario provides a manifestation of the different types of social identity of the participants, as well as a variety of social stereotypes: age, gender, professional etc. The game is tested on business communication classes with hearing impaired students and with hearing students.